Linking sustainable food systems and dietary diversity among agricultural communities: an ESG-based analysis - Chen, Sihan; Hafeez, Abida; Arshad, Muhammad (Frontiers in Sustainable Food Systems, 2025)
BackgroundFood and nutritional security are pivotal for sustainable development in developing countries. Dietary diversity is an essential aspect of food and nutritional security. Sustainable food systems play a significant role in achieving food and nutrition security. In this context, the Environmental, Social, and Governance (ESG) framework is a comprehensive approach to transitioning to sustainable food systems and climate resilience. However, scant empirical evidence exists on the link between particular ESG-compatible practices of farmers and their diet diversity in developing countries. ESG in agriculture drives sustainable food production by promoting environmental responsibility, social equity, and transparent governance.ObjectivesTherefore, the core objective of this study was to link ESG in agriculture to the diet diversity of farmers in Pakistan.MethodologyData collected from 435 farmers through multistage purposive and random sampling techniques were analyzed using binary probit regression and propensity score matching.ResultsThe Simpson index showed an average diet diversity score of 0.74, and cereals were the main source of calorie provision to the agricultural households. Furthermore, farmers with large families consumed less diverse foods than those with small families. The findings also revealed that the ESG dimensions significantly affect the dietary diversity of agricultural households. In the environmental dimension, farmers adopting more sustainable farm practices were likely to have higher dietary diversity than those with less sustainable farm practices. In the social dimension, nutritional knowledge and women’s empowerment were significantly associated with household dietary diversity. Governance is also positively related to the dietary diversity of agricultural households. The propensity score matching results revealed that the adoption of a greater number of sustainable practices at the farm level results in better dietary diversity than those farmers with the adoption of a lower number of sustainable farming practices.ConclusionTherefore, agricultural policies should incorporate ESG-aligned strategies to improve dietary diversity in farming communities in developing countries.